Identification and characterization of bacteria isolated from blood cultures at KAUH in Irbid, Jordan - Nid’a Alshraiedeh, Majd Alzedan, Rawan Alsharedeh, Rasha Bani-Salameh, Majed Masadeh, Farah Atawneh, Enas Alrafayah, Toga Zghoul (Journal of Applied Pharmaceutical Science, 2023)
Bloodstream infections are common in hospitalized patients and are associated with high morbidity and mortality. This study aims to describe the prevalence and characteristics of the bacteria isolated from positive blood cultures in patients hospitalized at King Abdullah University Hospital in Jordan, including biofilm formation tendency, antibiotic susceptibilities, and the spread of resistance genes. In this study, a total of 200 bacteria isolated from blood samples were identified and studied. About 50.5% of bacteria were Gram-negatives comprising mainly Escherichia coli (E. coli) and Klebsiella pneumoniae (K. pneumoniae), and 49.5% were Gram-positives, represented mainly by coagulase-negative Staphylococci (CoNS). Multidrug resistance was found in 54% of Gram-negative and 73.7% of Gram-positive isolates. Regarding antibiotic resistance genes, blaSHV was the most frequent ß-lactamase, and blaVIM was the most frequent carbapenemase detected in Gram-negatives. MecA was the most frequent resistance gene found in CoNS and methicillin-resistant Staphylococcus aureus. Ninety-six isolates (48%) could form either strong, moderate, or weak biofilms. The minimum biofilm eradication concentration was higher than the minimum inhibitory concentration, increasing up to 1,000-fold. In conclusion, E. coli and Staphylococci represent the main causative agents for sepsis. The high frequency of antimicrobial resistance and biofilm formation in bacteremia-derived bacteria highlights the sepsis management challenge.